Interference Thinking Students’ to Solve Proportion Problems Based on Cognitive Style - Venia Nabyla Ainul Putri; Subanji Subanji; Santi Irawati (PRISMA, 2026)
Thinking interference is defined as a disruption in information processing caused by overlap between old and new knowledge, which can hinder students' problem solving. The purpose of this study is to describe the forms of interference junior high school students thinking in solving ratio problems, as viewed from the cognitive styles of Field Independent (FI) and Field Dependent (FD). This study employs a descriptive qualitative approach, with the research subjects being three seventh-grade junior high school students who are suspected of thinking interference. Research data were collected through the Group Embedded Figures Test (GEFT), a ratio quiz, and interviews. The data analysis techniques used in this study were data reduction, data display, and conclusion. The results showed that FI students experienced retroactive interference characterized by students using the reverse proportion procedure to solve equivalent proportion problems. FD students experienced retroactive interference characterized by students solving problems using the reverse proportion procedure in equivalent proportion problems, and FD students experienced proactive interference characterized by students solving problems using the equivalent proportion procedure in reverse proportion problems. This occurs due to the similarity in solution procedures between equivalent proportion and reverse proportion. This study shows that both cognitive styles contribute to the emergence of thinking errors in solving comparison problems when students do not re-evaluate the appropriateness of the procedure to the problem context.